(3fKQ GdLhgQ aj TQM MOjK CHj PQs - (3, eMeO Hf Ydj Hf eMeO Hf YHO Gddg, CHh YHO Gddg GdThcGfj , J (B1250 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdMOjK GdbOSi GdeQhi ef WQjb CHj PQ hZjQg fYe hjMQU YdjgG cd Pi Yde s
(3BNQgG (B:s
(3bhdg Mjf JfJgi eSFdI cd hGLH efge aCYWjJge eG SCdhfi gPG GdaUd bO JbOe TQMg eSJhai adG fWjd GdcdGe Ydjg hEdi gfG GfJgi GdTQM dMOjK CHj PQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B4 - (3U (B624s
Keywords: (3GdMOjK h GdeUWdMs